Trust and cooperation at a confluence of worlds: An experiment in Xinjiang, China - Zhe Zhang; Louis G. Putterman; Xu Zhang (Brown University, Department of Economics, 2018)
We study trust and willingness to cooperate among and between Uyghur and Han college students in Xinjiang, China, where tensions exist between the two ethnic groups. We conduct an incentivized laboratory-style decision-making experiment in which within and between group interactions occur among identifiable participants without traceability of individual decisions. We find that members of each ethnicity show favoritism towards those of their own ethnicity in both trust and cooperation and that communication enhances inter-ethnic cooperation significantly. We also find that Uyghur and Han subjects behave differently in their willingness to cooperate relative to trust, although both trust and trustworthiness positively correlate with willingness to cooperate on the individual level.
Keywords: C91; O15; D64; H41; 330; trust; cooperation; experiment; culture; ethnicity; discrimination